Handbook of Primary Care Ethics - Spicer, John; Papanikitas, Andrew (Taylor & Francis, 2017)
This enterprising collection spans the breadth of primary care in multiple ways. Contributions from general practitioners, philosophers, nurses, physiotherapists, dentists, health economists, educationalists, patients and others reflect the rich variety that makes up primary care. Authors embrace the uncertainty inherent in the day-to-day reality of primary care, and practical advice sits alongside heartfelt accounts of issues that challenge practitioners. There is something here for everyone, whether the reader is looking for guidance on duties in primary care, a framework for analysing a difficult consultation, insights into the voice of the patient, or an understanding of the economics of primary care.